EFEKTIVITAS PENDEKATAN PROBLEM POSING PADA MATERI ATURAN SINUS DAN COSINUS - Farly Galuh Saputra; Edy Yusmin; Asep Nursangaji (UNIVERSITAS TANJUNGPURA, 2020)
Based on the pre research at SMA Taruna Bumi Khatulistiwa, there was only 6 of 32 overall students categorized as active in mathematics class and the percentage of the number of students who passed the grade in trigonometry was only 59,37%. The solution for the problem above is try to apply problem posing approach in the class. The aim of this research is to explore the effectivity of problem posing approach in Sines and Cosines Rule at class X SMA Taruna Bumi Khatulistiwa. The research method used in this research is experimental method in the form of pre-experimental design. Based on the result of the research, learning implementation was categorized as good with the average score is 3.48. Students learning activity was categorized as active with the average percentage is 75.58%. Students learning passion grade was not classically satisfied with the percentage is 36% based to the number of students who successfully pased the passing grade. Lastly, students responds to learning process with the approach is considered positive with the percentage is 92.86%. It can be concluded that learning implementation with problem posing approach in Sines and Cosines Rule at class X SMA Taruna Bumi Khatulistiwa was not effective.Keywords: Effectivity, Problem Posing Approach, Sines Rule, dan Cosines Rule